A Systematic Literatur Review (SLR): Picture Books on the Speaking Skills of Elementary School Students - Rizkiyah, Maulidah; Wisudawati, Asih Widi (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This literature review is motivated by the fact that students' speaking skills in elementary schools are still relatively low. Speaking skills are very necessary for elementary school students, to increase their self-confidence. This review aims to identify the influence of picture storybooks on speaking skills in elementary school students. This review uses a systematic literature review method using PRISMA, which was carried out on 23 articles obtained from Google Scholar via Publish or Perish. Keywords in the article search are